Analytic Theology and Analytic Philosophy of Religion: What’s the difference? - Baker-Hytch, M (Center for Philosophy of Religion at the University of Notre Dame, 2016)
Analytic theology is often seen as an outgrowth of analytic philosophy of religion. It isn’t fully clear, however, whether it differs from analytic philosophy of religion in some important way. Is analytic theology really just a sub-field of analytic philosophy of religion, or can it be distinguished from the latter in virtue of fundamental differences at the level of subject matter or methodology? These are pressing questions for the burgeoning field of analytic theology. The aim of this article, then, will be to map out several forms that analytic theology might (and in some cases actually does) take before examining the extent to which each can be thought to be distinct from analytic philosophy of religion.